Factors Mitigating Firm-specific Information Asymmetry and Target Price Accuracy in India - Samie Ahmed Sayed; Latha Sreeram (Vikalpa, 2017)
Executive Summary Over the last decade, efforts have been made to improve the quality of financial reporting and corporate governance standards prevailing in emerging markets. Even after 20 years of globalization, emerging markets continue to trade as a separate class ( Bekaert & Harvey, 2014 ). On account of a weak regulatory environment, firm-specific information asymmetry is expected to be on the higher side as compared to developed markets. In such an environment, any factors which mitigate information asymmetry may help improve efficiency of information providers such as equity research analysts. The role of equity research analysts is to process financial information and provide estimates which may be used by investors to make informed investment decisions. This study investigates whether the factors which mitigate firm-specific information asymmetry improve analyst target price accuracy in India. We expect sophisticated financial intermediaries such as equity research analysts to produce more accurate target price forecasts for firms with higher frequency of corporate announcements, higher analyst coverage, and higher foreign institutional holdings. Past research suggests that these three factors reduce information asymmetry and this reduction could possibly help analysts produce superior results. Our results show that higher frequency of corporate announcements creates short-term noise which reduces target price accuracy at the end of one-year forecast horizon. Our findings reveal that higher analyst coverage leads to better flow of firm-specific private information and improves target price accuracy anytime during or at the end of one year. We report that higher foreign institutional holding possibly improves stock liquidity, attracting more traders, which eventually leads to better target price accuracy at the end of forecast horizon. Our key finding is that there is a reduction in firm-specific information asymmetry due to the presence of more number of analysts and higher percentage of institutional holding.